CONTENT AND CHARACTERISTICS OF TRAINING WITH YOUNG BOXERS - Abdullaev Mehriddin Junaydullayevich (Journals Park Publishing, 2022)
In this article, the work on the organization of training sessions with boxers aged 14-15 has been studied and scientifically analyzed and summarized.
Keywords: coach and athlete; young boxers; cport motivator